Aconselhamento linguageiro na aprendizagem de Libras como língua adicional à luz da teoria da complexidade - Marques, Anderson (2025)
This thesis examines the process of teaching and learning Brazilian Sign Language (Libras) as an additional language (PEALibras-LAd) through the lens of Complexity Theory (Larsen-Freeman & Cameron, 2008; Paiva, 2011), framing it as a Complex Adaptive System (CAS). Despite the growing visibility of Libras as an additional language in Brazil, research on its teaching from a complexity perspective remains scarce. The goal of this study is to investigate how language advising (LA) can contribute to PEALibras-LAd, particularly in fostering learner autonomy and motivation. The study was conducted in a Brazilian federal university with undergraduate students training to become translators and interpreters of Libras. Its objectives are to discuss the role of the language advisor in this process, reflect on the impact of motivation on learning, highlight the importance of autonomy, and analyze the articulation between advisor and language teacher. Methodologically, this qualitative and interpretivist research draws on Complex Thought Modeling (CTM), combining field notes with retrospective analysis (Larsen-Freeman, 2011). The researcher’s role as advisor enabled observation of PEALibras-LAd at multiple levels, bridging theory and practice. The analysis followed four stages: (1) construction of a CTM based on the advisor’s (self-)reflections; (2) modeling PEALibras-LAd as a CAS, with emphasis on language development, learning at the edge of chaos, and the tension between cartesian and complex curricula; (3) discussion of emergent hypotheses concerning motivation and autonomy; and (4) reflection on the relation between advisor and complex teacher. Findings indicate that PEALibras-LAd operates as a CAS that requires sensitivity to emergent dynamics, recognition of the advisor’s role as a mediator of reflection and support, and a teacher profile aligned with the advisor’s, capable of collaboratively promoting autonomy and motivation in Libras learners.